Community-acquired pneumonia associated with cytomegalovirus persistence: prevalence and peculiarities of clinical course - K. D. Chichirelo-Konstantynovych (Zaporožskij Medicinskij Žurnal)
The article discusses the problem of cytomegaloviral persistence asymptomatic course among young patients with community-acquired pneumonia and in healthy population group based on specific immunoglobulins M and G appearance in blood and antibody avidity value (the duration of persistent). The connection between viral persistence and prognosis of community-acquired pneumonia course (by pneumonia severity index in PORT) is also recognized.